2011
DOI: 10.1103/physrevstab.14.043501
|View full text |Cite
|
Sign up to set email alerts
|

Charge and fluence lifetime measurements of a dc high voltage GaAs photogun at high average current

Abstract: GaAs-based dc high voltage photoguns used at accelerators with extensive user programs must exhibit long photocathode operating lifetime. Achieving this goal represents a significant challenge for proposed high average current facilities that must operate at tens of milliamperes or more. This paper describes techniques to maintain good vacuum while delivering beam, and techniques that minimize the ill effects of ion bombardment, the dominant mechanism that reduces photocathode yield of a GaAs-based dc high vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 13 publications
3
43
0
Order By: Relevance
“…Previous tests with GaAs indicated that photocathode charge lifetime could be enhanced at the electrostatic center using this technique [11]. As shown in Fig.…”
Section: -7mentioning
confidence: 59%
See 4 more Smart Citations
“…Previous tests with GaAs indicated that photocathode charge lifetime could be enhanced at the electrostatic center using this technique [11]. As shown in Fig.…”
Section: -7mentioning
confidence: 59%
“…7 as a function of radial position of the laser beam relative to the electrostatic center of the photocathode. It was both surprising and disappointing that the charge lifetime of photocathode #1 was comparable to that of GaAs [11]. Furthermore, the charge lifetime was observed to improve as the laser position was moved radially outward, which suggested ion bombardment played a role in QE decay.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations